The voice of Australian chairman - Brown, Alistair; Astami, E. (The Center for Accounting and Management Development, Faculty of Economics University of Technology "Yogyakarta", 2006)
This paper uses textual and statistical analysis to examine the tone and diction of Chairmen's Reports of Australia's Top 100 listed companies. A pattern emerges from the analyses. The diction of chairmen is wordy and repetitive, narrow and technical; the tone is stale and shopworn, struck from a mould. Chairmen, it seems, are hacks. Textual analysis reveals that by using bromide, cliches, euphemisms, jargon, platitudes and verbiage, chairmen, on one level, are able to win over key financial readers who are familiar with this discourse, but, at the same time, ward off close attention by non-financial readers who may recoil at such techniques. Statistical analysis shows that size of the board of directors, size of the entity and return on investment are significant for explaining elevated diction. The implications for the Australian community is that by using tone and diction to elevate and obfuscate reports, chairmen successfully resist cries for higher standards of transparency.